POTENTIAL CONTRIBUTION OF ENERGETIC USEFUL DOMESTIC WASTE TO THE ENERGY SUPPLY OF LITHUANIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The energy potential of domestic waste in Lithuania is 1411 GWh annually. In the case of the introduction of an extensive material recycling of the domestic waste, this amount would be reduced to 727 GWh per annual. Two variants of thermal waste treatment processes were taken into consideration: incineration by great furnaces and gasification followed by the incineration in gas power plants. The calculation of the necessary capacities for the thermal treatment of the domestic waste of every district is based on the annual availability of the plants of 75 %. Finally 4 scenarios arise, considering both the incineration on grate furnaces and the gasification in combination with the current energy potential of domestic waste and the potential after the introduction of extensive material recycling possible in the future.